GWAS of important crops of Amaranthaceae family with special reference to Chenopodium: A review - Devi, Y L; Thongam, B; Devi, R J (Plant Science Today, 2025)
Wide association of genomes deals with identifying naturally occurring genetic variance with targeted traits or genes. Putative candidate genes had the capability for improvement in quality and resistance to biotic and abiotic stress by exploiting linkage disequilibrium. Plants of the Amaranthaceae family like Spinach, Amaranthus, Chenopodium, and Sugarbeet are packed with essential nutritional components and are resistant to several biotic and abiotic stress. Several candidate genes are identified for the improvement of floral development, early flowering, late flowering, bolting formation, and resistance to several biotic and abiotic stresses . Through GWAS study, the genetic basis of several complex trait phenotypes can be deciphered for important agricultural crop plants. Exploiting these plants through GWAS will allowed knowing the putative candidate genes present in them which could be identified and used for further improvement of the crops.